Exploration of Hypolipidemic Effects of Sterols from Pleurotus tuber-regium(Fr.) Sing Sclerotium - Chao Wang; Yuan Liu; Yuting Duan; Haiping Lin (Foods, 2025)
The extraction technology of sterol was confirmed by ethanol reflux and saponification in this study. The orthogonal test was employed to assess the impact of extraction time, solid–liquid ratio, ethanol concentration and extraction temperature on the yield of sterol extraction. Hyperlipidemia model mice were established by feeding a high-fat and -sugar diet, and different doses of sterol extracts were given to the mice by gavages. The optimal extraction conditions were identified as an extraction time of 80 min, a solid–liquid ratio of 1:10, an ethanol concentration of 95%, and an extraction temperature of 90 °C, resulting in a sterol concentration of 1.16 mg/g. Compared with the high-fat model group, the high-dose group significantly reduced body weight by 17.2%, liver weight by 30.9%, and serum low density lipoprotein cholesterol by 20.0% (p < 0.05), while serum total cholesterol (5.59 ± 0.48 vs. 5.68 ± 0.64 mmol/L) and high-density lipoprotein cholesterol (0.98 ± 0.05 vs. 0.93 ± 0.03 mmol/L) showed no significant changes compared to the model group.